Isolasi Senyawa Flavonoid Ekstrak Biji Pinang Merah (Areca vestiaria Giseke) Dan Uji Sitotoksiknya Melalui Uji Brine Shirimp Lethality Test (BSLT): Isolation of Flavonoid Compounds of Red Pinang's Seed Extract (Areca vestiaria Giseke) And Cytotoxic Test by Brine Shirimp Lethality Test (BSLT) - Febriyanto Rerung; Syariful Anam; Akhmad Khumaidi (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2017)
Cytotoxic test is one method to predict the development of compounds that are toxic to the cell that is an absolute requirement for anticancer drugs. The aim of this study is to isolate flavonoids and determine LC50 value of the activity of the Red Pinang seed extract (Areca vestiaria Giseke). Extracts prepared by maceration method using ethanol 96%. Isolation is done through a range of methods includes partitioning using n-hexane, a preliminary test using the color reagent and KLT, isolation by preparative thin layer chromatography, thin layer chromatography multi eluent, UV-Vis spectrophotometer analysis and cytotoxic test isolates. The results showed that isolates flavonoid seed extract of Red Pinang (Areca vestiaria Giseke) has the medium potential of being a cytotoxic agent with LC50 values of 583.445 ppm.